Changes in Ocular Surface Parameter After Intense Pulsed Light Therapy in Ocular Demodicosis: A Case Report: Poster Presentation - Case Report - Resident - Rizki Adi Santosa; Angga Fajriansyah; Elfa Ali Idrus; Patriotika Muslima; Arief Akhdestira Mustaram (Majalah Oftalmologi Indonesia, 2023)
Introduction : Demodex infestation may manifest as blepharitis and dry eye syndrome. Intense Pulsed Light (IPL) therapy is an emerging option for managing ocular demodicosis. Case Illustration : A 77-years-old woman complained of itch and watery eyes since four years ago. Meibomian pouting, telangiectasias, foamy secretions, and sleeves were identified in both eyelids. Right eye examination showed 52% and 42% meibomian dropout in the superior and inferior eyelid, respectively, Schirmer test 6 mm, lipid layer thickness (LLT) 43 nm, tear meniscus height (TMH) 0.36 mm, and non-invasive tear break-up time (NIBUT) 9.6 seconds. Left eye examination showed 65% and 56% meibomian dropout in the superior and inferior eyelid, respectively, Schirmer test 5 mm, LLT 66 nm, TMH 0.16 mm, and NIBUT 5.8 seconds. Demodex mites were identified during eyelash wet mount examination. She underwent four sessions of IPL. At the two-month follow-up, complaints were alleviated. Signs of blepharitis were subsided. Right eye examination showed 36% and 34% meibomian dropout in the superior and inferior eyelid, respectively, Schirmer's test 9 mm, LLT 68 nm, TMH 0.49 mm, and NIBUT 10.7 seconds. Left eye examination showed 25% and 35% meibomian dropout in the superior and inferior eyelid, respectively, Schirmer's test 9 mm, LLT >100 nm, TMH 0.9 mm, and NIBUT 6.2 seconds. Discussion : IPL has a role in managing ocular demodicosis by local inflammation control, meibum liquefaction, and meibomian glands photomodulation. IPL is also thought to directly eradicate Demodex mites. Conclusion : Improvement of ocular surface parameters was observed after IPL therapy in ocular demodicosis.